Interpersonal Rejection Sensitivity and Regulatory Focus Theory to Explain College Students' Class Engagement. (17th January 2012) - Roscheck, David; Schweinle, William E.
Abstract : The current study investigated the relationship between undergraduate students' sensitivity to rejection and their level of participation in positive classroom engagement. One hundred and thirty-five undergraduate students from an upper-Midwest university volunteered to participate in a survey as part of their Psychology 101 course. As hypothesized, there was a negative correlation between students' sensitivity to rejection and their level of participation in positive class behaviors. We also found that this relationship was moderated by the regulatory focus, "prevention pride". The greater a student's prevention pride was, the more likely the student was to have an average amount of participation in positive class behaviors, regardless of their sensitivity to rejection. These findings suggest that students who do not become engaged in positive classroom behaviors may be afraid to do so for fear of rejection by peers and/or instructors, and that this relationship is moderated to a large degree by the students' prevention pride.